Stigmatization of Overweight and Obese Peers among Children - Di Pasquale, Roberta; Celsi, Laura (Frontiers in Psychology, 2017)
Children get involved in social categorization. Thus, they are able to stigmatize peers as well as to show in-group favoritism theorized by Tajfel and Turner (1986). Moreover, according to Aboud’s Cognitive-Developmental Theory (1988, 2003) the intensity of children’s stereotypes and negative attitudes towards socially devalued group members changes with age, in line with their cognitive development. In our Western society, which addresses especially females with the message that thinness is beauty, self-efficacy, power and success, being overweight or obese is one of the most socially devalued and stigmatized conditions among children. Thus, overweight and obese children are more likely to be personally and socially devalued compared to their average size peers. Starting with these theoretical reflections, the objectives of this mini-review are to examine if: 1) obese children show in-group favoritism and thus show less anti-fat attitudes than their thin and normal weight peers; 2) fat stigma is more prevalent toward overweight and obese girls than toward boys; 3) the intensity of weight-related stigma changes with the cognitive development of children.